Comparative evaluation of aspheric toric intraocular lens implantation and limbal relaxing incisions in eyes with cataracts and ≤3 dioptres of astigmatism. Issue 2 (18th June 2015) - Lam, Douglas K T; Chow, Vanissa W S; Ye, Cong; Ng, Paul Ka-Fai; Wang, Zheng; Jhanji, Vishal
Abstract : Purpose: To compare the visual outcomes of aspheric toric intraocular lens (IOL) implantation and limbal relaxing incisions (LRI) for management of coexisting age-related cataracts and astigmatism. Methods: In this prospective study, sixty eyes of 60 patients with visually significant cataract and coexisting corneal astigmatism ≤3 dioptres (D) were randomised to undergo phacoemulsification with either aspheric toric IOL or aspheric monofocal IOL with LRI. The main outcome measures were postoperative 3-month uncorrected visual acuity (UCVA), contrast sensitivity, rotational stability of the toric IOL and spectacle independence. Results: The postoperative UCVA, contrast sensitivity and refractive astigmatism were significantly better than the baseline measurements for both groups (p≤0.001). There was no significant difference detected for these parameters between LRI and toric IOL groups postoperatively (p≥0.119). At both postoperative month 1 and 3, the percentages of eyes in need of spectacles were lower in toric group than LRI group (p≤0.030). IOL misalignment was noted in three eyes in the toric IOL group (mean misalignment 7.67±4.04°). On vector analysis, magnitude of error (ME) was negative in the LRI group indicating undercorrection, whereas the ME was close to zero for toric group. Conclusions: Both toric IOL implantation and LRI were effective in correcting corneal astigmatism ≤3 D during phacoemulsification, while LRI tended to undercorrect astigmatism.